Characteristics of the fatigue life (IT-FT) of the recycled base course at the controlled stresses state - Iwański, Marek; Buczyński, Przemysław; Mazurek, Grzegorz (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
The paper presents the results of the base coarse made in the cold deep recycling technology with the emulsion in aspect of its durability for a different tensile stress level. The recycled base design simulated a deep recycling process with materials from existing crushed bituminous pavement layers("in-situ" technology). While assessing the quality of the designed MCE mixture, the following physical and mechanical parameters were considered: void contents Vm, indirect tensile strength ITSDRY at 25oC, tensile strength ratio TSR, stiffness modulus Sm. Additionally, the evaluation of fatigue was done at three stress cases: 250 Pa, 400 Pa, 500 Pa. The impact of the vehicle axle load on the stress state in the base course was simulated. For the purpose of determining the pavement durability, one of the method of fatigue life test was used. The tests were done according to IT-FT, based on an indirect tensile test (ITT). This method was choosen because it exhibits good equivalence to the real road pavement behaviour.